2016
DOI: 10.1155/2016/1486824
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Peste des Petits Ruminants Viral RNA in Fecal Samples of Goats after an Outbreak in Punjab Province of Pakistan: A Longitudinal Study

Abstract: Peste des petits ruminants (PPR) is a highly contagious viral disease of domestic and wild small ruminants and thus has serious socioeconomic implications. In Pakistan, during the year 2012-2013, estimated losses due to PPR were worth Rs. 31.51 billions. Close contact between infected and susceptible animals is an important route of transmission of PPR. Therefore, carrier animals play an important role in unnoticed transmission of PPR. The objective of the study was to investigate the detection of PPR virus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Ocular excretion of the virus starts three days earlier 22 , so fecal samples have some disadvantages in this regard. However, PPRV genetic material could be detected in rectal swabs by RT-QPCR until the end of the experiment, confirming results obtained in previous studies 19 , 20 and suggesting that animals infected by the virus could be identified relatively early on and during the whole course of infection based on fecal samples.…”
Section: Discussionsupporting
confidence: 88%
“…Ocular excretion of the virus starts three days earlier 22 , so fecal samples have some disadvantages in this regard. However, PPRV genetic material could be detected in rectal swabs by RT-QPCR until the end of the experiment, confirming results obtained in previous studies 19 , 20 and suggesting that animals infected by the virus could be identified relatively early on and during the whole course of infection based on fecal samples.…”
Section: Discussionsupporting
confidence: 88%
“…Whilst nasal swabbing was most productive in terms of detecting viral nucleic acid, sampling other fomites also demonstrated the presence of viral RNA in samples. Of interest, the detection of viral nucleic acid in fecal samples can be used as non-invasive samples, particularly in wildlife sampling [15,27,28,29,30], albeit at a low viral RNA copy number, raises questions about viral shedding in fecal matter and whether this represents a potential mechanism of virus transmission. Certainly further studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are limited data (Wasee Ullah et al., ) regarding the successful isolation of infectious virus from faecal material and no attempts are currently documented as to the isolation of virus from milk. Therefore, samples which were positive in PCR were inoculated onto VDS cells and passaged.…”
Section: Resultsmentioning
confidence: 99%